Guidance and Counseling Strategy for Students with Special Needs in Pertiwi Inclusion Kindergarten in Metro City - Muhammad Yusuf (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2021)
Research on Counseling Strategies for students with special needs was carried out in order to provide an overview of how educational services are also provided optimally in accordance with the mandate of inclusive education services in Permendiknas no. 70 of 2009 concerning inclusive education in Indonesia. This type of research is field research with a descriptive approach, namely by presenting descriptive data about guidance and counseling strategies carried out at Pertiwi Kindergarten, Metro City. In this study it was found that the guidance and counseling strategy was carried out in three stages, namely the planning stage in the form of initial communication with the parents and then determining the observation period for three months.